Lactococcal 936-type phages and dairy fermentation problems: from detection to evolution and prevention - Mahony, Jennifer; Murphy, James; van Sinderen, Douwe (Frontiers in Microbiology, 2012)
The so-called 936-type phages are the most frequently encountered lactococcal phage species in dairy fermentations, where they cause slow or even failed fermentations with concomitant economic losses. Several dairy phage population studies, performed in different geographical locations, have detailed their dominance in dairy phage populations, while various phage-resistance mechanisms have been assessed in a bid to protect against this virulent phage group. The impact of thermal and chemical treatments on 936 phages is an important aspect for dairy technologists and has been assessed in several studies, and has indicated that these phages have adapted to better resist such treatments. The abundance of 936 phage genome sequences has permitted a focused view on genomic content and regions of variation, and the role of such variable regions in the evolution of these phages. Here, we present an overview on detection and global prevalence of the 936 phages, together with their tolerance to industrial treatments and anti-phage strategies. Furthermore, we present a comprehensive review on the comparative genomic analyses of members of this fascinating phage species.